INVESTIGATING THE FINANCIAL STRENGTH IN THE ENERGY SECTOR: A STUDY ON TGTDCL (American International Journal of Humanities, Arts and Social Sciences, 2022)
This study presents a descriptive study analyzing the financial strength of TGTDCL in the energy sector. The study examines various financial aspects, including shareholding pattern, annual turnover, net assets value per share, liquidity ratios, profitability ratios, working capital ratios, capital structure ratios, contribution to the national exchequer, and system loss reduction. Employing a descriptive research design, the study utilizes purposive sampling to select TGTDCL. Data is collected from TGTDCL's annual reports spanning 2017-18 to 2020-21 and analyzed using Ms Excel, incorporating descriptive statistics and ratio analysis. Findings indicate that TGTDCL's operations are influenced by government control. Nevertheless, the company exhibits consistent growth in annual turnover, indicating effectiveness in capitalizing on market opportunities and meeting gas demand. The upward trend in net assets value per share reflects growth of assets, benefiting shareholders. Additionally, positive liquidity ratios highlight improved financial health and effective short-term obligation management. However, profitability ratios reveal a decline in profit generation and conversion of revenues to earnings. The study emphasizes inventory management, enhanced collection processes, and optimized payment cycles for financial strengthening. Capital structure ratios underscore the need for managing debt levels and improving cash flow generation. TGTDCL's contributions to the national exchequer demonstrate financial responsibility and positive impact on the economy. Efforts in system loss reduction enhance operational efficiency and cost management. The findings contribute to understanding the financial landscape of the TGTDCL and offer insights for policymakers, industry practitioners, and researchers. Future research should consider qualitative factors and detailed financial data to comprehensively assess financial position of industries in the energy sector.